2021
DOI: 10.1111/febs.16054
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection and characterization of ancestral CYP11A1 enzymes

Abstract: Mitochondrial cytochromes P450 presumably originated from a common microsomal P450 ancestor. However, it is still unknown how ancient mitochondrial P450s were able to retain their oxygenase function following relocation to the mitochondrial matrix and later emerged as enzymes specialized for steroid hormone biosynthesis in vertebrates. Here, we used the approach of ancestral sequence reconstruction (ASR) to resurrect ancient CYP11A1 enzymes and characterize their unique biochemical properties. Two ancestral CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…Although the use of ASR to identify key developments in CYP specialization is well reported for animal CYPs (39)(40)(41)(42), our work highlights the usefulness of ASR and related methodologies for investigating CYP specialization in plant biosynthetic pathways. In light of the accumulating knowledge of plant specialized metabolism, the large number of CYPs in these pathways, and the burgeoning collections of genomic resources, ASR is emerging as a powerful tool to investigate how particular enzymes and the biosynthetic pathways they constitute have evolved through time.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%
“…Although the use of ASR to identify key developments in CYP specialization is well reported for animal CYPs (39)(40)(41)(42), our work highlights the usefulness of ASR and related methodologies for investigating CYP specialization in plant biosynthetic pathways. In light of the accumulating knowledge of plant specialized metabolism, the large number of CYPs in these pathways, and the burgeoning collections of genomic resources, ASR is emerging as a powerful tool to investigate how particular enzymes and the biosynthetic pathways they constitute have evolved through time.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%
“…Studies using the ancestral mutation method have assessed the stabilizing effect of one or a few ancestral residues and revealed hydrophobic packing, hydrogen bonding and the formation of ion pairs (39,44,47,56,57,99) to be important. In other mutagenesis studies residues in the ancestral proteins have been altered to abolish stability as a way of identifying important interactions (47,66,114). Thus, analysis of ancestral structures has provided complementary information to studies on proteins from thermophiles and underscored the importance of a variety of stabilizing interactions.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Different colors represent individual studies and for each phylogeny, directly related lineages are connected by solid lines. Sources in the order shown in the figure are: ( 41 , 42 , 43 , 45 , 47 , 48 , 49 , 63 , 64 , 97 , 109 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ). …”
Section: Asrmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to evaluate ancestral enzyme thermostability showed that ASR-sourced enzymes were associated with higher melting temperatures compared to their WT counterparts. However, in the majority of studies, this conclusion was drawn when comparing only a handful of WT and ASR enzymes ranging from 1 to 8 ASR catalysts. , ,,, Therefore, while it has been well documented in the literature that ASR can produce stabilized enzymes, it has not been clear how statistically significant this effect is. To our knowledge, the work presented here is the largest study that compares thermostability between a balanced number WT and ASR enzymes, 57 and 56, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%